Far-from-equilibrium quantum many-body dynamics - Gasenzer, Thomas; Keßler, Stefan; Pawlowski, Jan M. (The European physical journal. C, Particles and fields, 2010)
A theory of real-time quantum many-body dynamics is evaluated in detail. It is based on a generating functional of correlation functions where the closed time contour extends only to a given time. Expanding the contour from this time to a later time leads to a dynamic flow of the generating functional. This flow describes the dynamics of the system and has an explicit causal structure. In the present work it is evaluated within a vertex expansion of the effective action leading to time-evolution equations for Green functions. These equations are applicable for strongly interacting systems as well as for studying the late-time behavior of non-equilibrium time evolution. For the specific case of a bosonic NN\mathcal{N}-component φ4-theory with contact interactions an s-channel truncation is identified to yield equations identical to those derived from the 2PI effective action in next-to-leading order of a 1/N1/N1/\mathcal{N} expansion. The presented approach allows to directly obtain non-perturbative dynamic equations beyond the widely used 2PI approximations.